PENGARUH PAD, DAU, DAN DAK TERHADAP PERTUMBUHAN EKONOMI DAN KEMISKINAN DI KABUPATEN INDRAGIRI HULU - Fikri, Khusnul; Sudrajat, Usep; Remofa, Yudha (JURNAL MANAJEMEN DAN BISNIS, 2019)
This research is in Indragiri Hulu Regency. The sample of this study is the local government of Indragiri Hulu Regency. This research used  secondary data in the form of quantitative data that includes financial data on the realization of the regional budget, named local revenue data, general allocation funds, special allocation funds, economic growth and poverty. The data in this study were obtained from relevant agencies or agencies, called the Regional Income Board of Indragiri Hulu Regency and the Central Statistics Agency of Indragiri Hulu Regency directly to the office and online looking at the agency's website related to the research variables. The analytical tool used by the author is Two Stage Multiple Linear Regression Analysis with a quantitative approach with the help of SPSS Software Version 21. The results of the study can be concluded that: (1) Regional original income partially has no effect on economic growth. An increase in regional original income cannot increase economic growth. Vice versa, if the original regional income has decreased does not necessarily reduce economic growth. (2) Partial allocation funds generally have no effect on economic growth. If the general allocation fund increases, economic growth does not increase. And also, if the general allocation funds decline, economic growth does not decline. (3) Partial allocation funds have no effect on economic growth. If the special allocation fund has increased or decreased it does not have an impact on economic growth in the Regency of Indragiri Hulu. (4) Regional original income partially has no effect on poverty. This means that the higher or the amount of original regional income has not been able to reduce poverty in Indragiri Hulu Regency. (5) Public allocation funds partially do not affect poverty. This means that changes (increases / decreases) in general allocation funds in Indragiri Hulu Regency cannot reduce poverty. (6) Partially allocated funds do not partially affect poverty. If the special allocation fund has increased it may not necessarily reduce the number of poor people in Indragiri Hulu Regency, meaning that an increase in DAK every year cannot reduce the number of poor people. (7) Regional original income, general allocation funds, and special allocation funds jointly (simultaneously) do not affect economic growth. (8) Regional original income, general allocation funds, and special allocation funds jointly (simultaneously) do not affect poverty.